hnRNP F Complexes with Tristetraprolin and Stimulates ARE-mRNA Decay - Reznik, Boris (Public Library of Science, 2014)
The tristetraprolin (TTP) family of zinc-finger proteins, TTP, BRF1 and BRF2, regulate the stability of a subset of mRNAs containing 3′UTR AU-rich elements (AREs), including mRNAs coding for cytokines, transcription factors, and proto-oncogenes. To better understand the mechanism by which TTP-family proteins control mRNA stability in mammalian cells, we aimed to identify TTP- and BRF1-interacting proteins as potential TTP-family co-factors. This revealed hnRNP F as a prominent interactor of TTP and BRF1. While TTP, BRF1 and hnRNP F are all RNA binding proteins (RBPs), the interaction of hnRNP F with TTP and BRF1 is independent of RNA. Depletion of hnRNP F impairs the decay of a subset of TTP-substrate ARE-mRNAs by a mechanism independent of the extent of hnRNP F binding to the mRNA. Taken together, these findings implicate hnRNP F as a co-factor in a subset of TTP/BRF-mediated mRNA decay and highlight the importance of RBP cooperativity in mRNA regulation.